2017
DOI: 10.1038/s41529-017-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of corrosion fatigue and stress-corrosion cracking in a precipitation-hardened martensitic stainless steel

Abstract: Fracture mechanics-based testing was used to quantify the stress-corrosion cracking and corrosion fatigue behavior of a precipitation-hardened martensitic stainless steel (Custom 465-H950) in full immersion chloride-containing environments at two applied electrochemical potentials. A plateau in the cycle-based crack-growth kinetics (da/dN) was observed during fatigue loading at low ΔK and [Cl − ] at and above 0.6 M. Evaluation of the fracture morphology and frequency dependence of this plateau behavior reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 68 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…Burns et al carried out fracture-mechanics based testing to quantify corrosion fatigue and SCC behaviour of precipitate-hardened martensitic stainless steel (Custom 465) under full immersion in chloride containing environment with applied potential [4]. The alloy under investigation, Custom 465, is also a martensitic age-hardenable stainless steel originally designed to be used in the aerospace industry.…”
Section: Stress Corrosion Cracking Of Wrought 17-4 Ph Ssmentioning
confidence: 99%
“…Burns et al carried out fracture-mechanics based testing to quantify corrosion fatigue and SCC behaviour of precipitate-hardened martensitic stainless steel (Custom 465) under full immersion in chloride containing environment with applied potential [4]. The alloy under investigation, Custom 465, is also a martensitic age-hardenable stainless steel originally designed to be used in the aerospace industry.…”
Section: Stress Corrosion Cracking Of Wrought 17-4 Ph Ssmentioning
confidence: 99%
“…An example of the synergism of corrosion fatigue and stress corrosion cracking is the "ripple-loading-effect" (RLE), 3,22,23 which allows cracking below K ISCC . Rippleload tests are conducted at high R-ratio (>0.9), lowamplitude, fast-cyclic loading below ΔK TH .…”
Section: Film-rupture Hydrogen Environmentembrittlementmentioning
confidence: 99%
“…Superposition models, mostly variations on Wei-Landes, have been developed and applied to specific alloys and environments, with limited success. 36,37 As late as 2017 3 and 2018, 38 some proposed models continue to assume the "linear superposition" model first proposed by Wei and Landes. 34 The failure of superposition models is that they assume cycle-and time-dependent contributions are separable, operate in parallel, and are non-interacting.…”
Section: Superposition Modelsmentioning
confidence: 99%
“…Recent studies have shown that SCC and fatigue, i.e., cyclic loading, both are present at a time on many structures of metallic materials [25,26], and the SCC environment (load, environmental conditions, and material susceptibility) has many influences on the fatigue crack growth rate, and vice versa. As an example, strain-induced corrosion cracking (SICC) is used for the situation where cracking takes place under increasing load which may not be increasing necessarily monotonically, but also some cyclic variations are present at start-up and shut down situations of the plants [27]; also during smooth operation, both the loadings, i.e., fatigue (cyclic) and stress corrosion, are present.…”
Section: Introductionmentioning
confidence: 99%